Content analysis of the news in Pera Todorović’s Male novine - Aleksić, Dejan; Vidić, Lidija (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2014)
As in many other countries, foundation of daily press is tightly conected to politics and political situation in Serbia. Even tough first magazines and newspapers began to emerge a few decades earlyer, their release was periodical or irregular, where a newspaper itself was a political organ or had narrow spectrum of themes. It is only with the appearance of “Male novine“ that one can talk about the beggining of modern daily press. The content is devided in columns and following Pera Todorović’s idea, the newspaper were intended for a large audience. As this newspaper, considered the first of it’s kind, had several different columns as newspaper today also have, this paper has it’s focus on column “domaće vesti“. Analyzing this column from several aspects, the beggining and the development of modern journalism is followed, as well as the influence that Pera Todorović himself had od that matter. Also, this paper focuses it’s attention to the implicit impacts that had an important role in the forming of the first daily newspaper in our country. Key words: Male novine, Pera Todorović, internal affairs news, daily newspapers, journalism, Serbia